ECONOMIC POLICY UNCERTAINTY AND STOCK MARKET DEVELOPMENT IN NIGERIA - Segun Kamoru FAKUNMOJU (Modern Management Review)
Development in global space and Government interference in the day-to-day economic activities as well as stock market forces are responsible for steady spread of economic policies uncertainty (EPU) around the world. Even though uncertainty policies disturb sectors, economic agents respond to this uncertainty policies in different manners, specifically when provoked with an unforeseen shock. In light of this, the aim of the study focused on link between EPU and stock market development proxied with stock traded volume in Nigeria. Expost facto research design and quarterly data were employed within data scope year of 2010 to 2023. Finding revealed that economic uncertainty index, money supply, interest rate, crude oil prices significantly affect stock trade volume used as proxied for stock market development. Thus, the study concluded that domestic stock investors should diversified across sectors so as to lessen quantum of risk exposure from unpredictable macroeconomic policies from money supply, interest rate, crude oil prices in Nigeria.